Assessment of a youth climate empowerment program: Climate READY - R. L. Wellman; A. Henderson; R. Coleman; C. Hill; B. T. Davey (Geoscience Communication)
This article presents an in-depth assessment of a youth, climate empowerment program, called Climate READY – Climate Resilience Education and Action for Dedicated Youth. It was developed by the Florida Atlantic University Pine Jog Environmental Education Center (FAU Pine Jog) and funded by the National Oceanic and Atmospheric Administration (NOAA) Environmental Literacy Program. The program built climate literacy and community resilience through a three-semester dual-enrollment program (financed by grant no. NOAA-SEC-OED-2020-2006190). Most student participants (∼80 %) were from Title 1 high schools in low socio-economic communities vulnerable to extreme weather and environmental hazards in Palm Beach County, Florida (see definition in Appendix A). The main objectives of this program were to increase knowledge of south Florida's changing climate systems; teach and promote environmentally responsible behavior, which results in the stewardship of healthy ecosystems and a reduction in carbon consumption to mitigate future environmental risks; and empower students to act as agents of change within the community by teaching community members about local climate impacts and resilience strategies for extreme weather events. Important characteristics of the program included the following: Students ages 15 to 17 years old registered for the Climate READY Ambassador Institute (summer semester 1) built climate knowledge, explored NOAA Science on a Sphere technology, engaged with scientists and resilience experts, developed communication and advocacy skills, and learned about local resilience solutions. At the end of the course, these students were given completion certificates and the title Climate READY Ambassadors (CRAs). An after-school mentorship (fall semester 2) component paired new Climate READY Ambassadors with fourth- and fifth-grade after-school students ages 9 to 11 years old to build community resilience awareness through four structured lessons and the creation of storybooks. Lastly, community outreach (spring semester 3) provided ways for Climate READY Ambassadors to share local resilience strategies at public events and promoted civic engagement in climate solutions. Data were collected from all students in the form of pre- and post-assessment questionnaires during the 2022–2023 academic year. Summative statistics were analyzed for climate science knowledge, self-identity, self-efficacy, and sense of place. Climate READY Ambassadors felt more prepared, confident, and able to communicate within their communities about climate change, and many demonstrated a significantly better understanding of climate science concepts. After-school students showed a better understanding of climate change and were able to identify ways to help reduce the effects of climate change. Both groups of students benefitted from the Climate READY Ambassador mentorship, demonstrating learning by doing and learning by storytelling.